Effect on the physico-chemical properties of liberica green coffee beans under ambient storage - Ismail, I.; Anuar, Mohd Shamsul; Shamsuddin, Rosnah (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2013)
Green coffee beans are stored for a certain period and under certain conditions until they are finally utilized. The storage period may depend on customer demand while the storage conditions depend on where the coffee beans are stored. Thus, this research emphasizes the physico-chemical changes that occur in Liberica coffee beans during storage under the Malaysian climate (average temperature and relative humidity of 29.33ºC and 71.75% respectively). The changes in the physico-chemical (coffee size, mass, densities, colour, proximate analysis, sucrose, chlorogenic acid content) and microbiological (yeast and mould count) properties were evaluated during eight months of storage. After the storage, the physical properties of the coffee changed as the coffee beans expanded in size, reduced in mass and density and became brighter in colour. Changes in the chemical properties were also detected where the moisture decreased and the ash content increased. In addition, the sucrose level was found to decrease with a corresponding increase in chlorogenic acid. During storage, the counts of yeast and mould were reduced. Model equations describing the changes in the properties were developed. The overall conclusion was that the coffee beans reduced in quality during storage.